Correlações entre morfometria ovariana e hormônios em vacas zebus não prenhes - Chacur, M. G. M.; Oba, Eunice [UNESP]; Kronka, S. N. (SciELO Espana/Repisalud, 2009)
The study of ovarian morphometry is directly related to its practical applications to interpret the examination of the reproductive tract of the cow. The objective of this work was to study the ovarian morphometry collected in slaughterhouse and correlations between corpus luteum area, progesterone and cortisol in no pregnant zebu cows. One hundred fourteen pairs of ovaries were collected from slaughterhouse, measured in thickness, length, width and volume, diameter and volume of the follicle, diameter and area of the corpus luteum. Significative difference (p<0.05) were observed for widths of (1.95 cm and 1.83 cm) and volume (p<0.05) of 7.26 ml and 6.23 ml of left and right ovaries respectively. For size and volume of follicles, and diameter and area of the corpus luteum, there was no significative difference between the sides. There was correlation of 0.46 (p<0.01) between left ovary volume × luteum corpus area, in the presence of follicles with diameters equal or greater than 9 mm, the corpus luteum of the massive and protuberant type were present in 23 (43.39%) of 53 ovaries, predominating in relation to type of massive and incluse 16 (30.18%). There were no significative correlation between corpus luteum area × progesterone, corpus luteum area × cortisol and progesterone × cortisol. In conclusion, the presence of the included corpus luteum in zebu cows could result in error during the rectal palpationexam to estimate the ovarian activity.
Correlations between ovarian morphometry and hormones in no pregnant zebu cows
Keywords: Corpus luteum; Cortisol; Follicle; Progesterone; Slaughterhouse; Bos indicus